Confirmation of Tuntun Angin (Elaeocarpus floribundus) Taxonomic Status Using matK and ITS Sequences - Dewi Indriyani Roslim; Siti Khumairoh; Herman Herman (Biosaintifika: Journal of Biology & Biology Education, 2016)
Tuntun angin is one of important floodplain plants in and around Kajuik Lake located in Riau Province, Indonesia. Morphological identification shows that the scientific name of this plant is Elaeocarpus floribundus. The study aimed to confirm the taxonomic status of tuntun angin using matK and nuclear intergenic spacer (ITS) sequences. The methods included fresh leaf DNA isolation, polymerase chain reaction, electrophoresis, sequencing, and data analysis using BLASTn program and MEGA software version 6.06 programs. The results showed that the matK sequence (519 bp) of tuntun angin had highest similarity to E. floribundus matK sequence that was available in GenBank. It was supported by the high max score (937), low E-value (0.0), high identity value (100%), and high query cover (100%). However, the ITS sequence of tuntun angin did not show similarity to E. floribundus ITS sequence because there was no database of the sequence in GenBank. This study was able to confirm the taxonomic status of tuntun angin as E. floribundus using matK sequence and also showed that morphological and molecular identification techniques were complementary to each other. Moreover, this study enriched the DNA sequence database of E. floribundus in GenBank which will be useful for this species’ molecular identification.How to CiteRoslim, D. I., Khumairoh, S. Herman, H. (2016). Confirmation of Tuntun Angin (Elaeocarpus floribundus) Taxonomic Status Using matK and ITS Sequences. Biosaintifika: Journal of Biology Biology Education, 8(3), 393-400.